2017
DOI: 10.3389/fmats.2017.00031
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Digital Volume Correlation Approaches for Strain Analysis in Bone Imaged with Micro-Computed Tomography at Different Dimensional Levels

Abstract: Accurate measurement of local strain in heterogeneous and anisotropic bone tissue is fundamental to understand the pathophysiology of musculoskeletal diseases, to evaluate the effect of interventions from preclinical studies, and to optimize the design and delivery of biomaterials. Digital volume correlation (DVC) can be used to measure the three-dimensional displacement and strain fields from micro-computed tomography (μCT) images of loaded specimens. However, this approach is affected by the quality of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 54 publications
6
98
0
Order By: Relevance
“…The excluded TS23 sample was used to evaluate the uncertainties in the displacement predictions by registering two pairs of repeated scans of the whole prenatal femur and tibia following a procedure used for different bone structures [26, 27]. The precision of the method was evaluated for the three Cartesian directions using the standard deviation of the displacement components over the whole registration grid for tibia and femur.…”
Section: Methodsmentioning
confidence: 99%
“…The excluded TS23 sample was used to evaluate the uncertainties in the displacement predictions by registering two pairs of repeated scans of the whole prenatal femur and tibia following a procedure used for different bone structures [26, 27]. The precision of the method was evaluated for the three Cartesian directions using the standard deviation of the displacement components over the whole registration grid for tibia and femur.…”
Section: Methodsmentioning
confidence: 99%
“…Since the first application of DVC, strain has been mapped in different bone types and scaffold implants. To approach tissue‐level strains, high‐resolution scans using synchrotron radiation should be taken to resolve textural details within the bone (Dall'Ara et al ., ). These studies have demonstrated the importance of ensuring that appropriate local texture is available for reliable subvolume tracking, and tuning DVC parameters to image texture.…”
Section: Tracking Microstructure To Map Local Strainmentioning
confidence: 97%
“…However, laboratory micro‐CT phase contrast approaches do not provide a large enough field of view to image the whole small animal organs at the required resolution. Synchrotron imaging has a larger field of view and has been shown to give lower tracking uncertainties for image correlation when compared to laboratory micro‐CT (Dall'Ara et al ., ). The considerably bright synchrotron X‐rays are able to obtain higher signal:noise reconstructions and shorter scans times.…”
Section: Outlook: Volumetric Strain Measurement In Soft Tissuementioning
confidence: 97%
See 1 more Smart Citation
“…Measurement errors are typically quantified on repeated scans (i.e. in a known deformation field such as ‘zero‐strain’) to account for the intrinsic noise of the input images (Dall'Ara et al ., ; Dall'Ara et al ., ). This repeated scan methodology has been already adopted to quantify strain errors associated with bone‐biomaterial interfaces (i.e.…”
Section: Introductionmentioning
confidence: 97%